2010
DOI: 10.1111/j.1346-8138.2010.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito allergy: Clinical features and natural course

Abstract: Mosquito bite allergic reactions are due to sensitization to mosquito salivary proteins. The purpose of our study was to assess the clinical features of Thai patients with mosquito allergy, and to define the natural desensitization course. Seventy patients with mosquito allergy were enrolled. Most patients were female. Half of the patients had a personal history of atopy. The average age of onset of mosquito reaction was 5.7 years old (range 2-58). Four patients were in the desensitization phase in which clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
1
29
0
2
Order By: Relevance
“…1 Sensitization to mosquito bites is common in the United States, Canada, Japan, Switzerland, and Finland, 2e4 sometimes causing severe systemic reactions, such as generalized urticaria, angioedema, wheezing, and even anaphylaxis. 1,5,6 Several allergens from the genera Aedes, Culex, and…”
Section: Introductionmentioning
confidence: 99%
“…1 Sensitization to mosquito bites is common in the United States, Canada, Japan, Switzerland, and Finland, 2e4 sometimes causing severe systemic reactions, such as generalized urticaria, angioedema, wheezing, and even anaphylaxis. 1,5,6 Several allergens from the genera Aedes, Culex, and…”
Section: Introductionmentioning
confidence: 99%
“…Manifestations of mosquito allergy are variable and depend on the route of exposure. When the contact with the allergens occurs via skin bites (saliva allergens), the symptoms consist of mild or severe local or systemic reactions [1,2,3,4]. However, evidence suggests that the inhalation of mosquito emanations and detritus deposited in house dust may induce allergic respiratory symptoms such as allergic asthma and rhinitis [5].…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of mosquito allergy suggests that after prolonged exposure to mosquito bites, desensitization may occur. This is accompanied by a decrease in the serum levels of specific IgE and an increase in specific IgG antibodies [21,48]. The abundance of A. communis in Finland in the summer is accompanied by increasing levels of IgE, IgG1 and IgG4 in the population.…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%
“…In a population of children from Winnipeg, Man., Canada, high levels of specific IgE and IgG occurred in the first 6 months, but had decreased by adolescence, suggesting that these children were desensitized naturally by exposure [57]. Kulthanan et al [21] showed the required interval between sensitization and desensitization in a population in Thailand to be approximately 4 years.…”
Section: Immunological Basis Of the Allergic Reactions Produced By Momentioning
confidence: 99%
See 1 more Smart Citation